Research on traffic identification and scheduling based on optical interconnection architecture in data center - Bingli GUO; Ning ZHAO; Zhiwen ZHU; Fan NING; Shanguo HUANG (Tongxin xuebao)
In order to solve the data center link congestion problem,based on the characteristics of the flow distribution and flow types,a flow identification and scheduling scheme based on optical interconnect structure,named HCFD (host-controller flow detection),was proposed to identify the elephant flow which has a large impact on the network performance,and use the SDN controller to make forward strategy,and schedule the network traffic reasonably.The implementation of the scheme was to use the Netfilter framework in Linux kernel protocol on the host side to mark the flow that exceeds the threshold amount.Then,the classification model was used in the controller side to classify the marked flow.Finally,the appropriate forwarding strategy was developed based on the above results.With the advantage of the photoelectric network,mechanisms of flow depth fusion and switching could be realized.The scheme which integrates the advantage of the existing research results,was expected to identify elephant flow more accurately and comprehensively.It can effectively alleviate the network congestion,make full use of network bandwidth,reduce end-to-end delay and packet loss rate.